2017
DOI: 10.1007/s00590-017-1927-7
|View full text |Cite
|
Sign up to set email alerts
|

Shoulder hemiarthroplasty for proximal humeral fractures: analysis of clinical and radiographic outcomes at midterm follow-up: a series of 51 patients

Abstract: Shoulder hemiarthroplasty has historically been the gold standard treatment for proximal humeral fractures not suitable to open reduction and internal fixation. In the last decades, reverse shoulder arthroplasty has gained more and more importance. Aim of this study is to retrospectively analyze subjective and objective outcomes of a group of consecutive patients. Fifty-one patients were evaluated with a mean follow-up of 18 months (range 12-60). For all the cases, the same surgical technique was performed in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 39 publications
0
11
1
Order By: Relevance
“…The patient satisfaction self-assessment scale was used in a study of 51 patients, with a mean age of 71 years and of whom 39 were female, who were treated with SHA for 3- or 4-part proximal humeral fractures (Valenti et al. 2017). This study found that 13 of 51 patients reported poor satisfaction after 18 months.…”
Section: Discussionmentioning
confidence: 99%
“…The patient satisfaction self-assessment scale was used in a study of 51 patients, with a mean age of 71 years and of whom 39 were female, who were treated with SHA for 3- or 4-part proximal humeral fractures (Valenti et al. 2017). This study found that 13 of 51 patients reported poor satisfaction after 18 months.…”
Section: Discussionmentioning
confidence: 99%
“…Xavier et al thought that cavity defects in proximal humerus were an indication to abandon internal fixation and to choose the method of prosthetic replacement [ 54 ]. So recently, hemiarthroplasty has been recommended as a good option for the treatment displaced PHF, especially with elderly patients [ 55 57 ]. However, high complication rates and poor functional results have been reported by the method because of tuberosity malreduction or migration, postoperative pain and instability [ 58 , 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…By studying a process, improvements can be applied to the most appropriate aspect of the process and outcomes can be evaluated and measured. For example, the outcomes of the patients with calcaneal fractures can be ensured [10], the risk of bleeding of hip fracture patients taking clopidrogel can be estimated [11], the use of antiosteoporotic medication in elderly patients with fragility pelvic fractures can be classified [12], and traditional treatments in trauma can be revisited [13][14][15][16][17][18].…”
Section: Orthopaedic Trauma Research In Healthcarementioning
confidence: 99%